2012
DOI: 10.1242/dmm.008623
|View full text |Cite
|
Sign up to set email alerts
|

Flower-deficient mice have reduced susceptibility to skin papilloma formation

Abstract: SUMMARYSkin papillomas arise as a result of clonal expansion of mutant cells. It has been proposed that the expansion of pretumoral cell clones is propelled not only by the increased proliferation capacity of mutant cells, but also by active cell selection. Previous studies in Drosophila describe a clonal selection process mediated by the Flower (Fwe) protein, whereby cells that express certain Fwe isoforms are recognized and forced to undergo apoptosis. It was further shown that knock down of fwe expression i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 33 publications
0
43
0
Order By: Relevance
“…The corollary in loser cells is the upregulation of the protein SPARC (secreted protein acidic and rich in cysteine), which transiently protects losers from being eliminated by apoptosis [22]. Both Flower and SPARC have been recently related with cancer in the context of cell competition [23,24], supporting the connection between the competitive process and tumor formation [19]. Specifically, Flower-deficient mice have been shown to present a significant reduction of skin papilloma formation upon the tumorigenic agent 7,12-dimethylbenz[a]-anthracene/12-O-tetradecanoylphorbol-13-acetate (DMBA/TPA) treatment, supporting the idea that the Flower code is evolutionary conserved and plays a role in tumor expansion [24] (for a recent review see [25]).…”
Section: Recent Discoveriesmentioning
confidence: 99%
See 1 more Smart Citation
“…The corollary in loser cells is the upregulation of the protein SPARC (secreted protein acidic and rich in cysteine), which transiently protects losers from being eliminated by apoptosis [22]. Both Flower and SPARC have been recently related with cancer in the context of cell competition [23,24], supporting the connection between the competitive process and tumor formation [19]. Specifically, Flower-deficient mice have been shown to present a significant reduction of skin papilloma formation upon the tumorigenic agent 7,12-dimethylbenz[a]-anthracene/12-O-tetradecanoylphorbol-13-acetate (DMBA/TPA) treatment, supporting the idea that the Flower code is evolutionary conserved and plays a role in tumor expansion [24] (for a recent review see [25]).…”
Section: Recent Discoveriesmentioning
confidence: 99%
“…Both Flower and SPARC have been recently related with cancer in the context of cell competition [23,24], supporting the connection between the competitive process and tumor formation [19]. Specifically, Flower-deficient mice have been shown to present a significant reduction of skin papilloma formation upon the tumorigenic agent 7,12-dimethylbenz[a]-anthracene/12-O-tetradecanoylphorbol-13-acetate (DMBA/TPA) treatment, supporting the idea that the Flower code is evolutionary conserved and plays a role in tumor expansion [24] (for a recent review see [25]). Complementarily, SPARC has been shown to be highly expressed in normal tissues at the boundaries of neoplastic lesions (as in the ductal adenocarcinoma and mucinous cystic neoplasia of the pancreas) and in tumor areas (such as in adenoma and adenocarcinoma of the colon and urothelial carcinoma) [23].…”
Section: Recent Discoveriesmentioning
confidence: 99%
“…Interestingly, this phenomenon was also seen in several human tumor types, suggesting that this pathway may be a highly relevant cell competition pathway involved in human malignancies (Petrova et al, 2012 (Eichenlaub and Cohen, 2016;Froldi et al, 2010;Hogan et al, 2011;Kucinski et al, 2016). However, whether cell competition plays a role in mammalian systems has been studied minimally (Petrova et al, 2012).…”
Section: Cell Competition Is a Developmental Mechanism To Ensure Tissmentioning
confidence: 98%
“…Profiling of cells undergoing Myc competition revealed that the membrane protein Flower and the secreted SPARC mediate cell competition (Portela et al, 2010;Rhiner et al, 2010). Flower expression is up regulated in some papillomas and Flower-null mice have an increased susceptibility to papilloma formation (Petrova et al, 2012). Additionally, SPARC's role in cancer has been known for some time but it seems to be more convoluted since in some cases it promotes cancer while in other cases it suppresses progression (Chlenski and Cohn, 2010;Petrova et al, 2011).…”
Section: Cell Competition In Cancermentioning
confidence: 99%
See 1 more Smart Citation